(untitled) (Vietnam Journal of Community Medicine, 2025)
Objectives: To evaluate the association between the Neer classification on X-ray and functional outcomes of the shoulder after locking plate osteosynthesis in patients with closed surgical neck fractures of the humerus. Subjects and methods: A cross-sectional descriptive study with longitudinal follow-up was conducted on 51 patients aged 18 years with closed surgical neck fractures of the humerus treated by locking plate osteosynthesis at Military Hospital 175 from January 2023 to June 2025. Preoperative X-rays determined Neer’s classification. Functional outcomes were assessed using the Constant-Murley score at 6 months postoperatively. Results: After 6 months, the mean Constant-Murley score reached 70.36 ± 7.36, with most patients achieving good or excellent shoulder function. There was no statistically significant difference in Constant-Murley scores between Neer fracture types (2-part: 70.72 ± 7.10 points; 3-part: 68.20 ± 7.91 points; 4-part: 73.39 ± 6.10 points; p > 0.05). Use of heavy suture or calcar screw also showed no significant effect on functional outcome. Age was the only independent risk factor negatively correlated with the Constant-Murley score (r = -0.696, p < 0.05). Anatomic neck-shaft angle restoration moderately improved outcomes (r = 0.3617, p < 0.05). The complication rate was low (1.96%). Conclusion: Locking plate osteosynthesis for closed surgical neck fractures of the humerus provides good functional recovery regardless of Neer classification if surgical techniq